The presence of Navarre in the Marraja Brotherhood and in the Treasure of Cartagena de Levante (1745-1773) - Montojo Montojo, Vicente (Huarte de San Juan. Geografía e Historia, 2018)
Alicante, Cartagena, Lorca and Murcia, cities of the kingdoms of Valencia and Murcia, witnessed between 1730 and 1773 the installation of some official Navarre Finance or income, as the customs in the first population, which in the case of Cartagena left a greater trace for his performance in the Brotherhood of Jesus Nazareno. These Navarre were related above all with the provision of supplies of the galleys of Spain and the North African presidios, and therefore with the Navarrese assiestants of the court. Those had business with the Béarnaise merchants of Cartagena, a characteristic group of its trade, in addition to the Genoese.
Keywords: social history; history of the administration; history of Spain; Cartagena